“It's a fight to get anything you need” — Accessing care in the community from the perspectives of people with multimorbidity - Ho, Julia W. (Health Expect, 2017)
BACKGROUND: There is a growing interest in redesigning health‐care systems to better manage the increasing numbers of people with multimorbidity. Knowing how patients experience health‐care delivery and what they need from the health‐care system are critical pieces of evidence that can be used to guide health system reforms. OBJECTIVE: The purpose of this study was to understand the challenges patients with multimorbidity face in accessing care in the community, and the implications for patients and their families. METHODS: A secondary analysis of qualitative data was conducted on semi‐structured interviews with 116 patients who were receiving care in an urban rehabilitation facility in 2011. Exploratory interpretive analysis was used to identify themes about access to care. RESULTS: Challenges occurred at two levels: at the health system level and at the individual (patient) level. Issues at the health system level fell into two broad categories: availability of services (failing to qualify, coping with wait times, struggling with scarcity and negotiating the location of care) and service delivery (unreliable care, unmet needs, incongruent care and inflexible care). Challenges at the patient level fell into the themes of logistics of accessing care and financial strain. Patients interacted and responded to these challenges by: managing the system, making personal sacrifices, substituting with informal care, and resigning to system constraints. CONCLUSION: Identifying the barriers patients encounter and the lengths they go to in order to access care highlights areas where policy initiatives can focus to develop appropriate and supportive services that are more person and family‐centred.